Biotechnology in Europe and Latin America: prospects for co-operation - Cantley, Mark (SciELO Books - Centro Edelstein, 2010)
The materials presented at the conference have been updated and edited, to give in this book an up-to-date picture of capabilities and common IV interests. Although inevitably any book on biotechnology is obsolete by the time it appears, there is nothing obsolescent about the dynamism now being displayed in the development of the bioindustries in both continents. We hope that the presentations assembled in this volume will testify to this dynamic development, and stimulate its further promotion. [excerpt taken from the book's Preface]